2014
DOI: 10.1108/nlw-03-2014-0029
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the prevailing images in library and information science profession: is the landscape changing?

Abstract: Purpose – This paper aims to provide a systematic review on library and information science (LIS) profession’s image and stereotypes from 1999 to 2013. In particular, it aims to identify and analyze the prevailing images of librarians in various contexts and explore possible changes occurring over time. Design/methodology/approach – The method of systematic review is adopted to identify the prevailing images in LIS profession. Specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
2
9
1
Order By: Relevance
“…For example, the status issue is still very important for information professionals (Vassilakaki & Moniarou-Papaconstantinou, 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For example, the status issue is still very important for information professionals (Vassilakaki & Moniarou-Papaconstantinou, 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In the 20 th century, librarians felt compelled to professionalize in order to increase respect, funding, standardisation, teamwork, and succession planning (Liestman, 2003, p. 41). The attention on who librarians are and what they do has not diminished, as there continues to be an extensive amount of literature regarding librarian images and stereotypes (Pagowsky & DeFrain, 2014;Posner, 2003;Kneale, 2009;Radford & Radford, 2001;Vassilakaki & Moniarou-Papaconstantinou, 2014). The subject also has grown new dimensions as modern society grapples with questions of identity, equitability, and the changing information landscape (Scherdin, 1994).…”
Section: Context For the Overall Studymentioning
confidence: 99%
“…Same is valid regarding the image of librarians and the stereotypical assumptions around their job (Luthmann, 2007). A literature review found that negative perceptions prevail and their work is misunderstood (Vassilakaki;Moniarou-Papaconstantinou, 2014). Particularly, the emotional factor attached to the personal relationship with (potential) users is of relevance (Consonni, 2010;Coker, 1993;).…”
Section: Contextmentioning
confidence: 99%